5 GHz Optical Front End in 0.35um CMOS - Li, Mengxiong (2007)
With the advantages of low cost, low power consumption, high reliability and potential for large scale integration, CMOS monolithically integrated active pixel chips have significant application in optical sensing systems. The optical front end presented in this thesis will have application in Optical Scanning Acoustic Microscope System (O-SAM), which involves a totally non-contact method of acquiring images of the interaction between surface acoustic waves (SAWs) and a solid material to be characterized.